ChemInform Abstract: Direct Catalytic Access to N‐Silylated Enamines from Enolizable Imines and Hydrosilanes by Base‐Free Dehydrogenative Si—N Coupling. Issue 6 (23rd January 2015) - Hermeke, Julia; Klare, Hendrik F. T.; Oestreich, Martin
Abstract A new procedure for the synthesis of otherwise difficult‐to‐make N‐silylated enamines is described.